Analyzing middle school science books according to the next generation science standards - Al-Sadi, Ameer Mohammed Ali Rasool; Awad, Omar Falah (Al-Adab Journal, 2022)
The research aimed to identify the extent to which the content of science books for middle school includes science standards for the next generation. Examining Arab and foreign studies related to these standards, and their validity was verified by presenting them to a group of experts specialized in the field of education / methods of teaching science, and thus the list consisted of three basic areas (scientific and engineering practices - comprehensive concepts - basic ideas) and stems from them (27) criteria, and the researchers analyzed the content of science books for the intermediate stage scheduled for the academic year (2018-2019) according to these criteria, with a number of pages (470) out of (493), The two researchers adopted both the explicit and implicit ideas, a unit for recording and repetition, and a unit for counting. The researchers extracted the validity of the analysis; This was done through the assistance of two experts specializing in education/science teaching methods, who analyzed a random sample of the content, and then presented the analyzed material and science standards for the next generation to the two experts, and they unanimously agreed on the validity of the analysis. Then they extracted stability over time and stability between analysts. The research found that all the basic dimensions of the standards were included in the science books of the intermediate stage, and that the science book for the first intermediate grade was more frequent than the science book of the second intermediate grade.